(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Demonetization is the latest buzzword in the country. The demonetization of 500 and 1000 banknotes was a policy enacted by the Government of India on 8 November 2016, ceasing the usage of all 500 and 1000 banknotes of the Mahatma Gandhi Series as legal tender in India from 9 November 2016. Its impact will be felt by every Indian in some or the other manner. Demonetization technically is a liquidity shock i.e. sudden stop in terms of currency availability. It is not a big disaster like global banking sector crisis of 2007.Every coin has two sides and the Demonetization too. On one hand millions of people are facing the heat of severe cash crunch and on the other hand so many people are getting Other than this a group of people including money launderer, brokers, policemen etc are making money illegally.